Analysis of pile driving and pile load test data in the Bangkok area - Vallop Suwansunthorn; Brenner, R.P.; Balasubramaniam, A.S.; Akagi, Toshinobu; The Federal Republic of Germany (Bangkok : Asian Institute of Technology, 1979)
Pile load test dat a and associated pile driving records and soil information were collected from 31 projects in the Bangkok area. There were 71 tests carried out to failure consisting of 64 compression loading tests and 7 tension loading tests. The piles tested were 47 driven prestressed concrete piles, 5 steel piles and 7 cast in-situ piles. The concrete piles were of various shapes and cross-sectional areas. Dutch cone tests were also carried out at six sites where load tests were in progress. The data were analyzed with respect to ultimate bearing capacity by various methods and compared with the observed ultimate carrying capacities. The methods used included the total stress method, the use of pile driving formulae, the wave equation analysis, Van der Veen's method using Dutch cone penetration tests, and methods employing the load-settlement characteristics to predict the failure load of tests not carried to failure, i . e. Bullen's , Chin's, Mazurkiewicz's, Davisson' s , Hansen's and Fuller & Hoy' s procedures. The analysis revealed that predictions using the total stress method, the results from Dutch cone tests or wave equation analysis correlated fairly wei1 with the observed failure loads. For predicting the ultimate load from load tests not carried out to failure Mazurkiewicz' s method yielded by far the best correlation.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1979
Keywords: Piling (Civil engineering) -- Testing